Risks in Technological Systems - Grimvall, Göran; Holmgren, Åke; Jacobsson, Per; Thedéen, Torbjörn (Springer Series in Reliability Engineering,, 2010)
Risks in Technological Systems is an interdisciplinary university textbook and a book for the educated reader on the risks of today's society. In order to understand and analyse risks associated with the engineering systems on which modern society relies, other concerns have to be addressed, besides technical aspects. In contrast to many academic textbooks dealing with technological risks, this book has a unique interdisciplinary character that presents technological risks in their own context. Twenty-four scientists have come together to present their views on risks in technological systems. Their scientific disciplines cover not only engineering, economics and medicine, but also history, psychology, literature and philosophy. Taken together these contributions provide a broad, but accurate, interdisciplinary introduction to a field of increasing global interest, as well as rich opportunities to achieve in-depth knowledge of the subject. The book is important reading for those who have to consider risks in their professional career, as well as for everyone who wants to develop a well-informed opinion of what is reasonable to believe when reading media reports on various risks. In addition to being a university textbook, Risks in Technological Systems is an engaging read for policy makers, politicians, psychologists, and planners, as well as the general reader. Springer Series in Reliability Engineering publishes high-quality books in important areas of current theoretical research and development in reliability, and in areas that bridge the gap between theory and application in areas of interest to practitioners in industry, laboratories, business, and government.